Informasi : peraturan perundang undangan Pemerintah Daerah Daerah Istimewa Yogyakarta (2019) - Informasi_:_peraturan_perundang_undangan_Pemerintah_Daerah_Daerah_Istimewa_Yogyakarta_(2019) (Biro Hukum Setda DIY, 2019)
st,2/irh,jil.1-2,c.1